IMPLEMENTASI PRINSIP MANAJEMEN PENDIDIKAN AGAMA ISLAM DI PONDOK PESANTREN DARUL HUDA BUAY PEMACA OKU SELATAN - Sighit Imanul Mustaqim (UNISAN JURNAL, 2024)
The aim of this research is to determine the implementation of Islamic boarding school-based management in an effort to improve the learning process. From the results of the author's initial observations at the Darul Huda Islamic Boarding School, the author found data that the level of student learning achievement was still low and needed to be improved again. Of course, this is the responsibility of the teacher as the learning manager and the madrasa head as the education manager at a madrasa. This research uses field research using analytical descriptive methods. The method the author used to collect data for this research was observation, interview and documentation methods. This analysis is used to reveal research results related to the implementation of Islamic boarding school-based management in an effort to improve the learning process at Riyadlotul Ulum Islamic boarding school. Based on the data that the author obtained, the author feels that the problem of increasing student learning achievement is a problem worthy of research. The efforts made by the Madrasah head are to improve the discipline of teachers and employees, motivate teachers by providing rewards for each activity, evaluate the activities of teachers, administration, head and deputy head of the Madrasah. Meanwhile, the efforts made by teachers are by providing motivation to students, providing study guidance, holding try outs, following up on learning outcomes such as remedial and enrichment, providing exercises and so on. However, the efforts made by the teachers and head of the Madrasah have apparently not been able to improve the learning achievement of students at the Darul Huda Islamic Boarding School as a whole and significantly.